2023
DOI: 10.3390/cancers15194723
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34 Family in Cancers: Role, Mechanism, and Therapeutic Potential

Junjiang Fu,
Saber Imani,
Mei-Yi Wu
et al.

Abstract: MicroRNA (miRNA) are small noncoding RNAs that play vital roles in post-transcriptional gene regulation by inhibiting mRNA translation or promoting mRNA degradation. The dysregulation of miRNA has been implicated in numerous human diseases, including cancers. miR-34 family members (miR-34s), including miR-34a, miR-34b, and miR-34c, have emerged as the most extensively studied tumor-suppressive miRNAs. In this comprehensive review, we aim to provide an overview of the major signaling pathways and gene networks … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 186 publications
0
6
0
Order By: Relevance
“…Similar to circRNAs, miRNAs belong to the non-coding RNA family. In contrast to circRNAs, miRNAs specifically bind to the 3′-UTR region of downstream target mRNAs, thereby facilitating mRNA degradation or suppressing their protein translation (Fu et al 2023 ). In this research, NEDD4L was identified as a downstream target gene regulated by miR-665.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to circRNAs, miRNAs belong to the non-coding RNA family. In contrast to circRNAs, miRNAs specifically bind to the 3′-UTR region of downstream target mRNAs, thereby facilitating mRNA degradation or suppressing their protein translation (Fu et al 2023 ). In this research, NEDD4L was identified as a downstream target gene regulated by miR-665.…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a acts differently in colorectal cancer compared to its role in prostate cancer, according to its interaction with tissue-specific cofactors and targets [ 193 ].…”
Section: Tissue-specific Roles Of Mirnas In Cancermentioning
confidence: 99%
“…miR-34a, directly transactivated by p53, influences tumor cells and impacts immune cells by modulating cytokine profiles and T-cell activation, critical for immune surveillance and antitumor immunity [ 193 , 199 ].…”
Section: Role Of Mirnas In Modulating Immune Cell Dynamics In the Can...mentioning
confidence: 99%
“…Research is still ongoing to improve the accessibility of miR-34 family members in translational research and clinical practice in respect to the treatment of breast cancer [41], colon cancer [42], lung cancer [43], oral cancer [44], oesophageal cancer [45] and some others (reviewed in [46]).…”
Section: Functions Of Small Non-coding Rnas and Their Modulation By E...mentioning
confidence: 99%